2020
DOI: 10.1192/bjo.2020.37
|View full text |Cite
|
Sign up to set email alerts
|

Development of the RMT20, a composite screener to identify common mental disorders

Abstract: Background There are few very brief measures that accurately identify multiple common mental disorders. Aims The aim of this study was to develop and assess the psychometric properties of a new composite measure to screen for five common mental disorders. Method Two cross-sectional psychometric surveys were used to develop (n = 3175) and validate (n = 3620) the new measure, the Rapid Measurement Toolkit-20 (RMT20) against diagnostic criteria. The RMT20 was tested agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Symptoms of generalized anxiety disorder (GAD), social anxiety disorder (SAD), panic disorder (PD), PTSD and major depressive disorder (MDD) are assessed using the Rapid Measurement Toolkit-20 ( RMT-20 ) ( Batterham et al, 2020 ). The RMT-20 is a self-report questionnaire with five times four items, rated on a scale of 1 (never) to 5 (always), assessing the severity of each disorder.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of generalized anxiety disorder (GAD), social anxiety disorder (SAD), panic disorder (PD), PTSD and major depressive disorder (MDD) are assessed using the Rapid Measurement Toolkit-20 ( RMT-20 ) ( Batterham et al, 2020 ). The RMT-20 is a self-report questionnaire with five times four items, rated on a scale of 1 (never) to 5 (always), assessing the severity of each disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate higher anxiety or depression severity. The RMT-20 has high internal consistency and excellent sensitivity and specificity ( Batterham et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…To harmonize our findings with those of other Wellcome Trust grants, we included three measures as secondary outcome measures: the World Health Organization Disability Assessment Schedule 2.0-Brief (WHODAS 2.0-Brief; [99]), GAD-7 [137] and the panic, social anxiety and PTSD subscales of the Rapid Measurement Toolkit (RMT20; [138]). The WHODAS 2.0-Brief is a 12-item survey that assesses overall role functioning across major life domains.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…The GAD-7 is a commonly used measure of generalized anxiety symptoms. The RMT20 is a brief screening tool developed using IRT analyses and well validated against clinical diagnoses [ 138 ].…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…Adults (≥ 18 years) will be able to enrol in the study when they experience clinically relevant insomnia symptoms (ISI ≥10 (Morin, Belleville [41]) and clinically relevant complaints according to the RMT-20 [42]) or the BPD-C [43,44]) meeting at least one of the cut-offs on the subscales for PTSD (≥8), SAD (≥12), PD (≥9), GAD (≥11) and/or BPD (≥14). A clinically relevant increased score on RMT20-MDD subscale is not a sufficient inclusion criterion, because prior studies have shown the use of iCBT-I in various populations with MDD.…”
Section: Participantsmentioning
confidence: 99%